2016
DOI: 10.1007/s00251-016-0915-0
|View full text |Cite
|
Sign up to set email alerts
|

High genetic diversity and distribution of Bubu-DQA alleles in swamp buffaloes (Bubalus bubalis carabanesis): identification of new Bubu-DQA loci and haplotypes

Abstract: In this study, genetic diversity analysis of MHC class II-DQA locus helped in identification of 25 new Bubu-DQA nucleotide sequences in swamp buffaloes (Bubalus bubalis carabanesis, Bubu). Phylogenetic analysis revealed the distribution of the buffalo DQA sequences in two major clusters of DQA1 and DQA2 genes, sharing common lineages with corresponding cattle alleles, possibly due to trans-species evolution. However, a highly divergent sequence, Bubu-DQA*2501, homologous to cattle (BoLA) DQA3 allele, was ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Regarding MHC Class II genes, trans-species theory supports the hypothesis that MHC alleles preceded the origin of related species and survived through the speciation process [ 48 ]. Phylogenetic analysis of Bovidae DRB sequences also supports this theory [ 49 , 50 ]. Bearing this in mind, it is expected that domestic cattle BoLA-DRB3 diversity was present in the auroch population before the divergence of major bovine types.…”
Section: Discussionmentioning
confidence: 91%
“…Regarding MHC Class II genes, trans-species theory supports the hypothesis that MHC alleles preceded the origin of related species and survived through the speciation process [ 48 ]. Phylogenetic analysis of Bovidae DRB sequences also supports this theory [ 49 , 50 ]. Bearing this in mind, it is expected that domestic cattle BoLA-DRB3 diversity was present in the auroch population before the divergence of major bovine types.…”
Section: Discussionmentioning
confidence: 91%
“…As a source of milk as well as meat, the water buffalo in South Asia is an important livestock species. Previously, we identified allelic variations and duplications in the DQA locus of swamp buffaloes . In this study, sequencing in the Murrah river buffalo identified novel allelic variants that may be relevant for tolerance to constant exposure of tropical pathogens.…”
Section: Source/descriptionmentioning
confidence: 85%